The Difference in Knowledge and Attitudes in Preventing Dental Caries Through Educational Cartoon Puppet Media - Adriyenni (CV. CENDIKIA JENIUS INDONESIA, 2024)
Dental and oral diseases, particularly dental caries, are common health issues, with a prevalence of 45.3% in Indonesia according to Riskesdas 2018. In the working area of Puskesmas Lubuk Alung, the highest cases of dental caries were found at SDN 01 Lubuk Alung. This study aims to determine the difference in knowledge and attitudes towards dental caries prevention after educational intervention using cartoon puppets. This research used a mixed-method approach with qualitative techniques through source triangulation and a quantitative quasi-experimental design with a one-group pretest-posttest approach, conducted from September 2023 to April 2024. The population consisted of 159 students, with a sample of 67 students selected using probability sampling and simple random sampling techniques. Data were collected through questionnaires and interviews with informants, including students, school health teachers, health professionals, language experts, and design experts. The data were analyzed using univariate and bivariate analysis with the Wilcoxon test.The results showed a significant increase in knowledge (from 11.54% to 14.61%) and attitudes (from 45.60% to 61.43%) after the educational intervention. The difference was statistically significant for both knowledge (p=0.001) and attitude (p=0.001). In conclusion, cartoon puppet media effectively improved students' knowledge and attitudes regarding dental caries prevention, and it is recommended to develop more comprehensive materials for different target groups.